2022
DOI: 10.3389/fmars.2022.800607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Stock Identification and Adaptability of Hatchery-Reared Black Rockfish, Sebastes schlegelii, Released Into the North Yellow Sea waters

Abstract: Successful stock enhancement refers to the maintenance of economic profit, whilst minimizing negative genetic and ecological effects. As hatchery environments differ from natural habitats, post-release identification of hatchery-reared juveniles, and estimation of their adaptability are essential steps in conducting responsible stock enhancement. The black rockfish is an important fishery species in Japan, South Korea and China. Overfishing has dramatically decreased natural resources and a stock enhancement p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…The Ho (0.174-0.273) was higher than He (0.173-0.234) in seven populations, indicating that the seven populations may be mixed with others and need further purification. Additionally, previous studies have reported the genetic diversity of S. schlegelii used to microsatellite DNA loci, 1,32 that the Ho, He, and PIC was much higher than this study. Recent studies have explored the genetic diversity of the black rockfish from a total of three populations in northern China using mtDNA loop analysis, and the results showed no significant genetic differentiation and low genetic differentiation.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…The Ho (0.174-0.273) was higher than He (0.173-0.234) in seven populations, indicating that the seven populations may be mixed with others and need further purification. Additionally, previous studies have reported the genetic diversity of S. schlegelii used to microsatellite DNA loci, 1,32 that the Ho, He, and PIC was much higher than this study. Recent studies have explored the genetic diversity of the black rockfish from a total of three populations in northern China using mtDNA loop analysis, and the results showed no significant genetic differentiation and low genetic differentiation.…”
Section: Discussioncontrasting
confidence: 66%
“…34 This is considered an adaptive mechanism to alleviate the constraints of limited individual exchange caused by short-distance migrations, which suggests that hatchery-reared fish can maintain a high level of genetic diversity. 1 The Fst and DR are essential parameters to measure the degree of genetic differentiation among populations. 35 In this study, the cultured population CDYZ showed moderate differentiation from the six wild populations, while the six wild populations showed low differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering its relatively shorter body length (67 mm) and consistent δ 13 C value in muscle aligned with the reef area isoscape, it is possible that summer Fish 1 might be a newly born individual within the reef area or could have originated from juvenile individuals released inshore. Notably, in China, between 2015 and 2019, over 30 million black rockfish were released in the Shandong Peninsula in the Bohai and Yellow Seas, driven by rapid growth in the hatchery industry and advances in aquaculture technology [44]. Stock enhancement activities for black rockfish were implemented between June and July, with the body length of released individuals measuring approximately 50 mm [45].…”
Section: Potential Sources For Non-resident Individualsmentioning
confidence: 99%